Monitoring Kualitas Air pada Tambak Pembesaran Udang Vannamei (Litopenaeus vannamei) di Situbondo, Jawa Timur [Monitoring of Water Quality on Rearing Ponds of Vannamei Shrimp (Litopenaeus vannamei) in Situbondo, Jawa Timur ] - Abdul Manan; Fatchurizal Rama Putra (Faculty of Fisheries and Marine Universitas Airlangga, 2014)
Abstract Vannamei shrimp (Litopenaeus vannamei) is one of fishery commodities that have high economic value in international market, so the vannamei shrimp farming can be reliable. Success in maintaining of water quality is the key factor in the cultivation. Either directly or indirectly, the water quality has important role in determining the growth and survival of vannamei shrimp. Water quality parameters that contribute to survival in vannamei shrimp growth include water temperature, dissolved oxygen, water pH, salinity and ammonia. The purposed of this study is to know the conditions of water quality on enlargement ponds of vannamei shrimp (Litopenaeus Vannamei) in Situbondo. Study was held on January 16 to February 16, 2012. The methods used in this study is descriptive method. Water management activities on enlargement vannamei shrimp includes good water quality observed in biological, physical, and chemical. In addition to the observation of water quality, maintenance, enlargement of vannamei shrimp also save good preparation includes construction of pond and container preparation and feeding. Daily observation data acquisition carried out water sampling done one time and early morning. Sampling using bottle samples. Get the data covering the temperature range between 27-30 ºC, salinity between 25-28 ppt, pH ranged from 7.0 to 9.0, DO levels ranged from 4.0 -4.8 mg / L, â‰¤ 0.001 ppm levels of ammonia, BOD from 1.3 to 1.75 ppm, plankton here tend to be kind Diatomae, Chlorella sp, Copepods, Rotifera, Ocylatoria.